(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
To investigate the effects of quetiapine on thyroid function tests in newly diagnosed schizophrenic patients. Thirty subjects with schizophrenia, were treated openly with quetiapine .Diagnosis of schizophrenia was made according to DSM-IV criteria of American Psychiatric Association. Another thirty healthy individual participated in the study as a control group. Thyroid data, consisting of values for thyroid-stimulating hormone (TSH), total triiodothyronine (TT3 ), and total thyroxine (TT4). TSH, TT3, and TT4 were measured by radioimmunoassay. Measurements of patient’s thyroid data were done before and after 3 months of therapy (Suggested period of the research) with quetiapine and at the start of the research for the controls. Comparison of TSH, TT3 and TT4 of the control group and those of patients before treatment shows a non significant differences for all parameters. Comparison between TSH, TT3 and TT4 values before and after treatment with quetiapine shows only a significant reduction of TT4 values (P<0.001). This study shows that 3 months therapy with quetiapine leads to a reduction of TT4 concentration in the serum of schizophrenic patients.